Recent Integrations of Latent Variable Network Modeling With Psychometric Models - Wang, Selena (Frontiers in Psychology, 2021)
The combination of network modeling and psychometric models has opened up exciting directions of research. However, there has been confusion surrounding network models, graphic models, latent variable models and their applications in psychology. In this paper, we attempt to remedy this gap by providing a comprehensive introduction of latent variable network models and their recent integration with psychometric models to both psychometricians and applied psychologists. Following this introduction, we summarize developments under network psychometrics and show how graphical models under this framework can be distinguished from other network models. Every model is introduced using united notations, and integrative models are discussed from both network and psychometric perspectives. All methods are accompanied by available open-source R packages inducive to further independent learning.